Penerapan Analisis Faktor dalam Menentukan Faktor-Faktor yang Mempengaruhi Keputusan Belanja Online Melalui Aplikasi Shopee (Studi Kasus: Mahasiswa Universitas Sumatera Utara) - Bunga Sakinah; Elly Rosmaini; Muhammad Romi Syahputra; Mardiningsih Mardiningsih (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Factor analysis is a statistical method aimed at exploring correlations or relationships among variables studied, which are then grouped into fewer new factors. Principal Component Analysis (PCA) is a statistical technique used to reduce the dimensions of data with the goal of identifying hidden patterns or significant structures within the data. The research results indicate the presence of 5 factors influencing the decision-making process in online shopping among students of the University of North Sumatra via Shopee, namely the Funding Application Factor (28.141%), Information Reputation Factor (13.983%), Communication Satisfaction Factor (7.452%), Types and Compensation Factor (6.683%), and Guarantees and Prices Factor (5.794%). These five factors obtained a cumulative variance of 62.051%, indicating that they influence online shopping decisions through Shopee among University of North Sumatra students by 62.051%.